Host-status and host-sensitivity of sweet potato cultivar 'blesbok' to meloidogyne javanica and related management strategies of meloidogyne inconita - Makhado, Ndemedzo Vincent (My University, 2020)
Root-knot (Meloidogyne species) nematodes are host to most plant species, with the success of most crops being dependent upon proper nematode management tactics. Sweet potato (Ipomoea batatas L.) is highly susceptible to root-knot nematodes, with physical damage being visible on roots. The withdrawal of highly effective fumigant synthetic nematicides from the agrochemical markets resulted in a need to investigate alternative strategies for managing high nematode population densities, with the use of nematode resistance being the most preferred strategy. The objectives of this study were (1) to establish whether sweet potato cv. 'Blesbok' would be resistant to M. javanica under greenhouse conditions, (2) to investigate whether cucurbitacin containing phytonematicides would be comparable to Velum synthetic nematicide in suppressing Meloidogyne species. For Objective 1, treatments comprised 0, 5, 25, 125, 625, 3125 and 15625 eggs and second-stage juveniles (J2), had six replications and validated in time. Uniform sweet potato cuttings were transplanted in 20-cm diameter plastic pots, filled with steam pasteurised (300°C for 1 hour) loam soil. At 56 days after inoculation, plant growth, plant nutrient and nematode variables were assessed using analysis of variance and subjected to lines of the best fit. Treatments had significant (P ≤ 0.05) effects on eggs and highly significant (P ≤ 0.01) effects on J2, final nematode population densities (Pf) and the reproductive factor (RF), contributing 39, 45, 42 and 92% in total treatment variation (TTV) of the respective variables. Treatments did not have significant effects on plant variables. Calcium, K, Mg and Fe versus M. javanica levels each exhibited negative quadratic relations, with the models being explained by associations from 59 to 96%. In contrast, Zn versus M. javanica levels exhibited positive quadratic relation, with the model being explained by 80 and 98% association and optimised at 125 M. javanica units. For Objective 2, four treatments, namely, untreated control, Nemarioc-AL phytonematicide, Nemafric-BL phytonematicide and Velum had 10 replications and also validated in time. The plantlets with well-developed root system were transplanted under field conditions. Data for Object 2 did not comply with the requirements for ANOVA and were therefore subjected to Principal Component Analysis (PCA). Nemafric-BL phytonematicide treatment in both experiments reduced eggs, J2 in roots and J2 in soil and RP of Meloidogyne species, with the results being comparable to those of Velum synthetic nematicide. Nemarioc-AL phytonematicide reduced J2 in roots and in soil of Meloidogyne species, without affecting eggs in roots and RP. Nemafric-BL phytonematicide and Velum each increased plant growth variables in Experiment 1 and Experiment 2, whereas Nemarioc-AL phytonematicide did not have significant effects on plant growth variables. Velum chemical nematicide stimulated the accumulation of most essential nutrient elements in leaf tissues of the test cultivar, followed by Nemafric-BL phytonematicide, whereas Nemarioc-AL phytonematicide had no significant effects on the accumulation of essential nutrient elements. The study had two major outcomes, namely, (1) that the efficacy of Nemafric-BL phytonematicide was comparable to that of Velum chemical nematicide in suppression of population densities of Meloidogyne species in cv. ′Blesbok′ under field conditions and (2) that cv. ′Blesbok′ was tolerant to M. javanica and therefore, it was not necessary to investigate the mechanisms of nematode resistance.
Thesis (M.A. Agriculture. (Plant Production)) -- University of Limpopo, 2021
Keywords: Root-knot; Nematodes; Plant species; Sweet potato; Root-knot nematodes; Southern root-knot nematode; Plant species